A study of tuberculosis in road traffic-killed badgers on the edge of the British bovine TB epidemic area. Issue 1 (December 2018) - Sandoval Barron, Elsa; Swift, Ben; Chantrey, Julian; Christley, Robert; Gardner, Richard; Jewell, Chris; McGrath, Ian; Mitchell, Andrew; O'Cathail, Colman; Prosser, Alison; Ridout, Sue; Sanchez-Cabezudo, Gonzalo; et al.
Abstract The role of badgers in the geographic expansion of the bovine tuberculosis (bTB) epidemic in England is unknown: indeed there have been few published studies of bTB in badgers outside of the Southwest of England where the infection is now endemic in cattle. Cheshire is now on the edge of the expanding area of England in which bTB is considered endemic in cattle. Previous studies, over a decade ago when bovine infection was rare in Cheshire, found no or only few infected badgers in the south eastern area of the county. In this study, carried out in 2014, road-killed badgers were collected through a network of local stakeholders (farmers, veterinarians, wildlife groups, government agencies), andMycobacterium bovis was isolated from 21% (20/94) badger carcasses. Furthermore, there was strong evidence for co-localisation ofM. bovis SB0129 (genotype 25) infection in both badgers and cattle herds at a county scale. While these findings suggest that both badgers and cattle are part of the same geographically expanding epidemic, the direction of any cross-species transmission and the drivers of this expansion cannot be determined. The study also demonstrated the utility of using road-killed badgers collected by stakeholders as a means of wildlife TB surveillance.